Thermal Challenges in Dynamic Infrared Thermography Used for Perforator Mapping - Lin, Olivia M.; Hunter-Smith, David J.; Rozen, Warren M. (Journal of Reconstructive Microsurgery, 2023)
Background The aim of this study is to investigate the different approaches to thermal challenges, both cold and warm, used in dynamic infrared thermography for reconstructive surgery, and explore whether it affects the success of preoperative perforator mapping.Methods Literature was collected from Ovid Medline, Embase, PubMed, and Cochrane. The references of the full-text articles located from the original search were also appraised. Thirteen articles were extracted for the final qualitative analysis. A systematic review was then conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines.Results Thirteen articles looked at a cold challenge, which included airflow cooling, direct contact cooling, and evaporation-based cooling. Two articles investigated warm challenges. One paper used no challenge, suggesting it unnecessary with a highly sensitive camera. All cold challenges were positively supported by a high level of flap perfusion success and/or a high level of correlation with other forms of investigation.Conclusion Cold challenges were overall superior to no challenge and warm challenges; however, this conclusion is limited by the small participant size, the possibility of detection bias, and poor methodology detailing. Airflow cooling—specifically, using a desktop fan to blow air for 2 minutes—was noted to likely cause the least discomfort due to a low cooling capacity yet simultaneously maintain effectiveness and allow for a uniform cooling application. Warm challenges showed less conclusive results and were restricted by lack of studies. This topic would benefit from larger scale studies that compare multiple approaches while using standardized equipment to eliminate confounding factors.
Keywords: dynamic infrared thermography; perforator mapping; surgery; thermal challenge